Altered chemokine receptor expression in the peripheral blood lymphocytes in polymyositis and dermatomyositis. (November 2017) - Zhu, Ziwei; Yang, Chunshu; Wang, Jianing; Feng, Qianhui; Chen, Qi; Yang, Pingting
Highlights: %CD4 + CXCR3 + and %CD8 + CXCR3 + cells decreased in DM, and %CD8 + CXCR3 + decreased in PM. %CD4 + CCR4 + and %CD8 + CCR4 + cells did not change in DM or PM. The Th1/Th2 ratio significantly decreased in DM. The serum level of CXCL10 negatively correlated with %CD4 + CXCR3 + cells in DM. %CD4 + CXCR3 + cells decreased more severely in the DM patients with ILD. Abstract: Objective: To examine the expression of chemokine receptors in different peripheral blood T-cell subsets in patients with polymyositis (PM) and dermatomyositis (DM). Methods: We used flow cytometry to measure the frequencies of chemokine receptors CXCR3 and CCR4 expression in the CD4 + or CD8 + lymphocytes. Enzyme linked immunosorbent assays were also used to measure the concentrations of C-X-C motif chemokine 10 (CXCL10), thymus and activation regulated chemokine (TARC) and macrophage derived chemokine (MDC). Results: Comparing to 20 healthy controls, %CD4 + CXCR3 + and %CD8 + CXCR3 + T cells significantly decreased in 33 DM patients, and %CD8 + CXCR3 + cells decreased in 24 PM patients, but %CD4 + CCR4 + and %CD8 + CCR4 + cells did not significantly change in both the PM and DM patients. Accordingly, the Th1/Th2 polarization, analyzed as the balance obtained after dividing %CD4 + CXCR3 + cells by %CD4 + CCR4 + cells, showed a significant reduction in DM. The serum concentration of CXCR3 + ligand, CXCL10, significantly increased and negatively correlated with circulating %CD4 + CXCR3 + cells in DM patients. There was no significant change of TARC and MDC in PM and DM patients. Furthermore, %CD4 + CXCR3 + cells decreased more severely in the patients with interstitial lung disease. Conclusions: The present results indicate that the distributions of circulating CXCR3 + T-cells differ among the PM and DM cases. Our findings suggest a pathogenic difference between PM and DM.